External Electric Field Dependent Photoinduced Charge Transfer in Donor-PC71BM System for an Organic Solar Cell (Journal of Atomic and Molecular Sciences, 2016)
We use time-dependent density functional theory together with a set of extensivemultidimensional visualization techniques to characterize the field-dependentelectronic structure and rate of photo-induced charge transfer in organic donor-acceptordyad. External electric field is incorporated into the generalized Mulliken-Hush modeland Marcus theory. We use these methods to evaluate the influence of the externalelectric field on the electronic coupling between donor and acceptor. We also calculatethe reorganization energy and the free energy change of the electron transfer. Thesetheoretical methods and calculation techniques proves that the external electric fieldhas main effect on the electron transfer rate. More important, our results provide anew framework to understand charge transfer of organic systems under the externalelectric field.
Keywords: external electric fields; light-induced charge transfer; electronic coupling; organic solar cell.